2008
DOI: 10.1016/j.virol.2008.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the integrase protein of coliphage HK022

Abstract: The integrase (Int) proteins of coliphages HK022 and lambda, are phosphorylated in one or more of their tyrosine residues. In Int of HK022 the phosphorylated residue(s) belong to its core-binding/catalytic domains. Wzc, a protein tyrosine kinase of Escherichia coli, is not required for Int phosphorylation in vivo, however, it can transphosphorylate the conserved Tyr(342) catalytic residue of Int in vitro. Int purified from cells that overexpress Wzc has a reduced activity in vitro. In vivo, the lysogenization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…While the small plaques and lower adsorption rate of the JACS-K mutant initially suggested that a single phosphorylation event is not optimal for infection to occur, the results for ⌽X174-100/101/102 suggest that additional conversion sites do not increase plaque size or adsorption rate. While lambda has several tyrosine residues that are phosphorylated during the lysogenic pathway, controlling the specific timing of cell lysis (13), it benefits by encoding a protein kinase that can autophosphorylate as well as dephosphorylate, allowing lambda to balance the lysogenization rate with its own growth rate (13). ⌽X174 does not encode a kinase, limiting its control of E. coli K-12 lysis.…”
Section: Vol 84 2010 Notes 4861mentioning
confidence: 99%
See 2 more Smart Citations
“…While the small plaques and lower adsorption rate of the JACS-K mutant initially suggested that a single phosphorylation event is not optimal for infection to occur, the results for ⌽X174-100/101/102 suggest that additional conversion sites do not increase plaque size or adsorption rate. While lambda has several tyrosine residues that are phosphorylated during the lysogenic pathway, controlling the specific timing of cell lysis (13), it benefits by encoding a protein kinase that can autophosphorylate as well as dephosphorylate, allowing lambda to balance the lysogenization rate with its own growth rate (13). ⌽X174 does not encode a kinase, limiting its control of E. coli K-12 lysis.…”
Section: Vol 84 2010 Notes 4861mentioning
confidence: 99%
“…Thus, the JACS-K mutant, in contrast with the JACS strain, has a very reactive threonine on its virion surface which can readily have its terminal hydroxyl group phosphorylated (13). In a recent study, it was found that the E. coli K-12 infecting coliphages HK022 and lambda are phosphorylated at one or more of their tyrosine residues (13), and the penetration of E. coli K-12 by these phages is dependent on the energy supplied by phosphorylation (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Escherichia coli Wzc and Bacillus subtilis PtkA BY-kinases were found to phosphorylate UDP-glucose dehydrogenase enzymes (4,5), EpsD from Streptococcus thermophilus (6) and Wzc of Klebsiella pneumoniae (7) were found to phosphorylate the undecaprenylphosphate glycosyltransferases EpsE and WcaJ, respectively, and Cap5B2 from Staphylococcus aureus was found to phosphorylate the UDP-acetyl-mannosamine dehydrogenase Cap5O (8). In addition, BY-kinases have been demonstrated to have other cellular targets not related to polysaccharide biosynthesis, as is the case for the E. coli alternative heat shock sigma factor RpoH and the RpoE anti-sigma factor RseA (9), integrase proteins (Int) of coliphage HK022 (10), and single-stranded DNA-binding proteins SsbA and SsbB from Bacillus subtilis (11). Besides the genetic and biochemical analyses of individual targets of BY-kinases reported above, other bacterial tyrosine-phosphorylated proteins have been identified by gel-free proteomics approaches in organisms such as E. coli (12), B. subtilis (13,14), Listeria monocytogenes (15), Streptococcus pneumoniae (16), and Pseudomonas species (17), to name a few.…”
mentioning
confidence: 99%
“…In E. coli, the BY-kinase Wzc was found to phosphorylate integrase proteins (Int) of coliphages HK022 and . Overexpression of Wzc in tyrosinephosphatase deficient background resulted in a significantly reduced lysogenization, indicating that phosphorylation of Int down-regulates its activity [30]. Following the finding that heat shock response in E. coli is modulated by the activity of the BY-kinase Etk [19], a link between tyrosine phosphorylation and heat shock was also published for B. subtilis.…”
mentioning
confidence: 94%